Optical solitons of (3 + 1) dimensional and coupled nonlinear Schrodinger equations (vol 54, 261, 2022) - Inan, Ibrahim Enam; İnç, Mustafa; Rezazadeh, Hadi; Akinyemi, Lanre (Springer, 2022)
[Abstract Not Available]